The importance of various aspects of communication with patient in palliative care - Stanicki, Paweł; Dobosz, Maciej; Chilimoniuk, Zuzanna; Wójcik, Piotr; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Communication is an important element of medical care at all its stages. It is particularly important in the care of terminally ill patients. Then the psychological support of the patients and their families seems to be a prime matter while taking care of them. The purpose of this study is to discuss important aspects in communication with a palliative patient such as start time of conversations, culturally sensitive communication, positive emotion communication (PEC), communication with a pediatric patient and talking about spirituality and beliefs. This analysis of scientific publications presents the current state of communication between doctors and patients and also provides guidance on what actions should be taken to improve it. The number of evidence showing the advantages of early and honest dialogue with terminally ill patients (especially pediatric patients) and their families is increasing. As a result of research on communication-based on positive emotions, it has been shown that it is equally important to relieve the negative emotions of the patient and to build a sense of strength and connection. Research shows that insufficient knowledge of clinicians prevents effective communication with culturally diverse patients. Almost all of the parents do not regret talking to their children about their deadly diseases. Supporting them makes it easier to accept the loss of their child and increases their satisfaction. Clearly defining the concept of spirituality can help physicians properly talk about religion and beliefs with patients.